On Statistical Comparison of Efficiencies of Fishing GearCOMPARISON OF EFFICIENCIES OF FISHING GEAR - Nair, A. K. Kesavan (Fishery Technology, 1986)
The distribution of fish caught by experimental gill nets has been found to be in the Poisson or Negative binomial form. Using this information, application of Chi-square test as suggested by Mood et al. (1974) has been illustrated, for comparing the efficiencies of gill nets. This test provides an alternative to Anova F-test especially in the context of significance of nonadditivity for the two-way model. Based on the present work and the findings by Nair (1982) and Nair & Alagaraja (1982, 1984) an outline approach for statistical comparison of the efficiencies of fishing gear is presented.